STUDIES ON ANTIBACTERIAL ACTIVITY OF CORDYCEPS MILITARIS (L.) LINK - POOJA PATHANIA,; ANAND SAGAR,; ANAND SAGAR, (International Journal of Pharma and Bio Sciences, 2014)
Antibacterial activity of aqueous and methanolic extracts of Cordyceps militaris was determined in-vitro against two pathogenic bacteria (Escherichia coli and Staphylococcus aureus) following agar well diffusion method using different concentrations (25, 50, 75 and 100%). Aqueous and methanolic extracts showed potant antibacterial activity against selected strains. Methanolic extract showed a maximum inhibitory effect against growth of each of the test bacterium. There is a need for further studies to isolate and characterize the antibacterial moieties in this fungus for practical disease control measures.